1991
DOI: 10.1152/ajpregu.1991.261.3.r690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous infusions of angiotensin II on muscle sympathetic nerve activity in humans

Abstract: The effect of angiotensin II (ANG II) on the sympathetic outflow was examined in normal humans. The mean arterial pressure and muscle sympathetic nerve activity (MSNA) were measured before and during intravenous infusions of phenylephrine (0.5 and 1.0 micrograms.kg-1.min-1) or ANG II (5, 10, and 20 ng.kg-1.min-1) for 15 min at 30-min intervals. The baroreflex slope for the relationship between the increases in mean arterial pressure and the reductions in MSNA was significantly less acute during the infusions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 0 publications
7
67
0
Order By: Relevance
“…In agreement with Noll et al, 26 who found unchanged muscle sympathetic nerve activity in conjunction with reduced diastolic blood pressure after oral short-term administration of captopril to healthy subjects, we found unchanged muscle sympathetic nerve activity after intravenous administration of enalaprilat, suggesting resetting of the baroreflex control of muscle sympathetic nerve activity to lower blood pressures. This notion is further supported by the findings of Matsukawa et al, 27 who examined muscle sympathetic nerve activity in healthy subjects during equipotent infusions of Ang II and phenylephrine. They found a dose-dependent reduction of muscle sympathetic nerve activity after Ang II that was smaller than during the infusion of phenylephrine.…”
Section: Discussionsupporting
confidence: 59%
“…In agreement with Noll et al, 26 who found unchanged muscle sympathetic nerve activity in conjunction with reduced diastolic blood pressure after oral short-term administration of captopril to healthy subjects, we found unchanged muscle sympathetic nerve activity after intravenous administration of enalaprilat, suggesting resetting of the baroreflex control of muscle sympathetic nerve activity to lower blood pressures. This notion is further supported by the findings of Matsukawa et al, 27 who examined muscle sympathetic nerve activity in healthy subjects during equipotent infusions of Ang II and phenylephrine. They found a dose-dependent reduction of muscle sympathetic nerve activity after Ang II that was smaller than during the infusion of phenylephrine.…”
Section: Discussionsupporting
confidence: 59%
“…As such, it is possible that angiotensin II could increase SNS activity in a similar manner in obese humans. Muscle sympathetic nerve activity increases with angiotensin II infusion (Matsukawa et al, 1991) and decreases with angiotensin converting enzyme inhibition (Miyajima et al, 1999) in normotensive humans. Furthermore, multiple components of the renin-angiotensin system are expressed in adipose tissue and angiotensinogen, the major substrate for angiotensin II formation, is expressed to a greater extent in visceral than subcutaneous adipocytes (Engeli et al, 2000).…”
Section: Potential Mechanisms Of Sympathetic Nervous System Activatiomentioning
confidence: 99%
“…It has been demonstrated that a high concentration of circulating Ang II is able to pass the blood-brain barrier and increase sympathetic outflow centrally. [43][44][45] However, losartan may also pass the blood-brain barrier and then bind to AT 1 receptors in the brain. 46,47 The central effects of Ang II on the sympathetic nervous system may be attenuated during chronic administration of losartan.…”
Section: Hyzaar and Absence Of Sympathetic Baroreflex Resettingmentioning
confidence: 99%